Areca-nut waste-derived carbon porous for sustainable electrode materials: A brief study for green-supercapacitor - Nursyafni, Nursyafni; Julnaidi, Julnaidi; Taer, Erman (Indonesian Physics Communication, 2024)
Biomass-based porous carbon is an exceptional material with unique nano-morphological properties and a high surface area, making it an ideal candidate for improving the performance of supercapacitor electrodes. Herein, activated carbon derived novel areca-nut waste (ANW) as electrodes materials were successfully produced using a simple method. The process involved drying the ANW using pre-carbonization, chemical activation, and high-temperature pyrolysis. The zinc chloride was selected as chemical catalytic in 1 m/l solution. Subsequently, porous carbon was produced at different physical activation temperatures of 800°C, 850°C, and 900°C. The activated carbon was converted into coin-like design with an additional adhesive of PVA. The electrochemical properties were assessed using a two-electrode system in a 1 M H2SO4 electrolyte. The ANW-based supercapacitor demonstrated good electrochemical performance, with an optimal specific capacitance of 94.6 F/g at 850°C. Additionally, it exhibited an optimal energy density of 12.8 Wh/kg and a power density of 245.516 W/kg. These results suggest that porous carbon derived from ANW biomass holds promise as a sustainable working electrode for green-supercapacitor.